Efficacy of Tui Na in idiopathic constipation in children with cerebral palsy: a randomized controlled clinical trial - Wang, Huijuan; Chen, Bichan; Long, Qian; Yang, Qiuping; Mao, Jiawen; Ma, Qinghua; Yi, Xingqian; Wang, Ying; Liu, Yinghan; Cao, Zhiliang; Xu, Jianda; Ye, Yong; et al. (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the efficacy and potential adverse events of Tuina therapy for idiopathic constipation in children with cerebral palsy (CP).MethodsA total of 60 CP children with idiopathic constipation were enrolled and randomly divided into Tuina and control groups. The control group was treated with basic treatment and 12 sessions of lactulose oral solution, whereas the Tuina group received basic treatment and 12 sessions of infantile Tuina treatment. The following parameters were compared: the Bristol stool form scale (BSFS), the Constipation Assessment Scale (CAS) and the improvement in constipation. In addition, adverse effects were recorded.ResultsAt 4 weeks after the final treatment, the percentage of infants whose constipation improved was 23 (76.7%) in the Tuina group and 21 (70.0%) in the control group (P = 0.771). Initially, the CAS score, weekly bowel movements and proportion of infants with bowel evacuation ≥2 h were comparable between the two groups (P > 0.05). At 4 weeks after the final treatment, the CAS score, weekly bowel movements and proportion of infants with bowel evacuation ≥2 h all significantly improved (P < 0.05) compared with those in the initial situation. However, no difference was found in either group at 4 weeks after the final treatment. No serious adverse reactions (such as diarrhea, abdominal pain, vomiting, subcutaneous redness, skin breakage, or syncope) were recorded.ConclusionsTuina was as effective as medical care in addition to basic treatment for both groups. The results of this study suggest that Tuina, as a nonpharmacological therapy, may be helpful as an alternative treatment for constipation. More advanced research and large-sample studies should be conducted.